Scrivere per immagini La tecnica del segno tra preistoria e cinema - Solla, Gianluca (Mechane, 2025)
The paper explores the hypothesis of images as foundation of human culture, starting from the analysis of Palaeolithic cave paintings. Far from being mere decorations, these figurative representations could be interpreted as primary forms of inscription of reality, grounded in a symbolic technology capable of transforming natural experience into a shared system of meanings. From this perspective, culture is understood as the faculty of generating signs and images endowed with semantic and communicative value, thus constituting an original matrix of collective memory.